If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 3 + 10x = -2 + 4x + 10 Reorder the terms: 3 + -1x + 10x = -2 + 4x + 10 Combine like terms: -1x + 10x = 9x 3 + 9x = -2 + 4x + 10 Reorder the terms: 3 + 9x = -2 + 10 + 4x Combine like terms: -2 + 10 = 8 3 + 9x = 8 + 4x Solving 3 + 9x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + 9x + -4x = 8 + 4x + -4x Combine like terms: 9x + -4x = 5x 3 + 5x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + 5x = 8 + 0 3 + 5x = 8 Add '-3' to each side of the equation. 3 + -3 + 5x = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 8 + -3 5x = 8 + -3 Combine like terms: 8 + -3 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 3x+1=41 | | 31=4t+3 | | x-x^2-x^3=0 | | -x^2=-3x+5 | | 750-50*24= | | -11/t=8/48 | | -3p+8=6-(8p+5) | | 16(2x-4)=4(8x+9) | | 6x+3+x=2+5x+5 | | 0.20t^2-45.0t+1000=0 | | 0.20t^2-45.0t=1000 | | 9+10s-4=9s+47-6s | | -16t^2+3t+1.3=0 | | -7(x+1)-13=26+3 | | -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 |